Inflammation and insulin resistance in adipose tissue - Sissel Åkra (Bioingeniøren, 2021)
Background. Adipose tissue is today well established as a complex and active endocrine organ. The adipose tissue secretes a number of cytokines, adipokines, which act both locally and systemically. The adipose tissue in normal weight people has anti-inflammatory properties, but in overweight / obesity the adipose tissue is exposed to various forms of cellular stress which results in increased production of pro-inflammatory cytokines. This causes a chronic low-grade inflammation that is associated with a number of metabolic diseases such as insulin resistance and type 2 diabetes and to atherosclerotic heart diseases.